FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN MENGKONSUMSI TABLET FE PADA IBU HAMIL DI PMB HUSNIYATI KOTA PALEMBANG - Inayah, Maudila; Puspita Sari, Erma; Rahmawati, Eka; Aisyah, Siti (JURNAL KESEHATAN INDRA HUSADA, 2024)
According to the World Health Organization (WHO), it was estimated 33% of people worldwide suffering from anemia, with iron deficiency identified as its primary cause, and Anemia is also recognized as a significant contributor to disability, with an annual prevalence rate of 9%. The purpose of this study is to determine the relationship between knowledge, family support, and the role of health workers simultaneously with adherence to taking Fe tablets in pregnant women at PMB Husniyati Palembang in 2024. This type of research was quantitative using analytic survey method with cross-sectional approach. The population in this study included all pregnant women who visited PMB Husniyati for antenatal care during the study period. The sample was obtained through accidental sampling. Data were analyzed with the chi-square statistical test. The results of univariate analysis showed that from 50 respondents, mothers with good knowledge were 42 respondents, mothers with poor knowledge were 8 respondents (16.0%), 32 mothers (64.0%) received positive family support, and 18 mothers (36.0%) received negative support, 40 respondents (80%) reported a good role of health workers, and 10 respondents (20%) who reported a poor role of health workers. The results of the bivariate analysis of the chi- square test showed that knowledge (p-value 0.014), family support (p-value 0.036), and the role of health workers (p- value 0.046). In conclusion, knowledge, family support, and the role of health workers were significantly associated with adherence to Fe tablet consumption among pregnant women at PMB Husniyati in 2024. The findings suggest that health workers should consider implementing Fe tablet monitoring cards to enhance adherence among pregnant women receiving these supplements.